Design of sliding mode control using SVPWM modulation method for speed control of induction motor - AK, AYÇA; OYMAN SERTELLER, NECİBE FÜSUN (My University, 2023)
The sliding mode control method is a highly accurate and easy-to-implement approach that can be effectively utilized in the control of high-dimensional nonlinear systems that operate under uncertain conditions. In this study based on Matlab/Simulink, a Proportional-Integral-Integral Sliding Mode Control (PI-ISMC) method has been developed to control the mechanical speed of a three-phase squirrel cage induction motor. The modeling of the induction motor and the design of the proposed controller have been conducted in the qd0 reference frame. The asymptotic speed tracking under uncertainty and different loading conditions has been ensured by tuning the parameters of the PI-ISMC controller. Additionally, field-oriented control (FOC) with space vector modulation has been applied to the same motor to evaluate the performance of the sliding mode control topology in induction motor control, and its performance has been compared with the sliding mode control method
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Induction Motor; SMC Control; FOC Control; Matlab/Simulink